Penerapan Model Problem Based Learning untuk Meningkatkan Aktivitas Belajar Siswa di Kelas IV Sekolah Dasar - Eca Sintia Reka; Elfia Sukma (e-Journal Inovasi Pembelajaran Sekolah Dasar, 2019)
This study attempts to improve student learning activities in integrated thematic learning through used the of Problem Based Learning (PBL) model to the fourth grade students of SDN 05 Bandar Buat. This is a PTK typified study with the implementation of two approaches, namely qualitative and quantitative. conducted in two cycles, with three meetings, covering four stages, namely planning, implementation, observation, and reflection. This study was conducted at SDN 05 Bandar Buat to 27 students. The results of the study: (1) percentage The learning plan, namely 80.35% (Good) to 94.44% (Very Good). (2) The implementation of learning from  aspect of teacher, of 80.35% (Good) to 92.85% (Very Good). (3)The aspects of students of 80.35% (good) to 92.85% (Very Good). (4) the student activities of 69.55% (enough) to 90.73% (Very Good). It can be concluded that the Problem Based Learning model can possibly improve student learning activities.Keywords: Problem Based Learning Model, student learning activities.